Heterometallic 3d–4d coordination polymers assembled from trans-[RuIII(L)(CN)2]− tectons and 3d cations. Issue 41 (17th June 2019) - Marinescu, Gabriela; Madalan, Augustin M.; Maxim, Catalin; Shova, Sergiu; Clérac, Rodolphe; Andruh, Marius
Abstract : Two families of magnetic heterometallic coordination polymers (1D and 2D) have been assembled using heteroleptic dicyanido-Ru III building blocks. Abstract : Five new cyanido-bridged heterometallic coordination polymers have been obtained by reacting PPh4 [Ru III (salpn)(CN)2 ]·H2 O (1 ) and AsPh4 [Ru III (valen)(CN)2 ]·8.5H2 O (2 ) (H2 salpn and H2 valen being Schiff-base proligands resulting from the condensation reaction of salicylaldehyde with 1, 3-propanediamine and, respectively, o -vanillin with 1, 2-ethanediamine) with divalent transition metal perchlorate salts: ∞1[{Ru III (salpn)(CN)2 }3 {M II (DMF)3 }2 ](ClO4 )·4DMF (M II = Mn, 3 ; Co, 4 ) and ∞2[{Ru III (valen)(CN)2 }4 {M II (DMF)3 }2 {M II (DMF)4 }](ClO4 )2 ·4DMF (M II = Mn, 5 ; Co, 6 ; Ni, 7 ), respectively. The dicyanido species, trans -[Ru(salpn)(CN)2 ] − and trans -[Ru(valen)(CN)2 ] −, act as metalloligands with the 3d metal ions. Compounds 3 and 4 are isostructural one-dimensional (1D) coordination polymers with a ladder topology. Each M II ion is hexacoordinated by three cyanido groups arising from three {Ru(salpn)(CN)2 } units and by the oxygen atoms from three DMF molecules, which are coordinated at meridional positions. Compounds 5–7 are also isostructural, their structures consisting of 2D networks with a herringbone topology. The magnetic susceptibility measurements of these 1D and 2D systems reveal the presence of dominating Ru III –M II antiferromagnetic (AF) interactions in compounds 3, 4, 5 and 6, while ferromagnetic Ru III –Ni II interactions are observed in 7 . All these compounds stay in their paramagnetic state down to 1.8 K except compound 4 which possesses a 3D ordered AF ground state.